2022
DOI: 10.1039/d2sc04533h
|View full text |Cite
|
Sign up to set email alerts
|

Electrification of a Milstein-type catalyst for alcohol reformation

Abstract: Novel energy and atom efficiency processes will be keys to develop the sustainable chemical industry of the future. Electrification could play an important role, by allowing to fine-tune energy input...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…61 This hypothesis is also supported by theoretical studies on thermal activated alcohol dehydrogenation, where ion-pairing transition states are oen proposed. 60,62,63 (4) Oxidation of hydride intermediate: the oxidation of the hydride intermediate is expected to be readily feasible at the applied potential as shown in our previous study 50 and could serve as thermodynamic driving force to regenerate active species. 64 These observations can be rationalized by the putative catalytic cycle proposed in Scheme 7 (see also ESI Section 8 †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 This hypothesis is also supported by theoretical studies on thermal activated alcohol dehydrogenation, where ion-pairing transition states are oen proposed. 60,62,63 (4) Oxidation of hydride intermediate: the oxidation of the hydride intermediate is expected to be readily feasible at the applied potential as shown in our previous study 50 and could serve as thermodynamic driving force to regenerate active species. 64 These observations can be rationalized by the putative catalytic cycle proposed in Scheme 7 (see also ESI Section 8 †).…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, we unravelled the beneficial role of electricity in promoting turnover at significantly lower temperatures, a breakthrough that holds promise to increase the energy-efficiency of such systems in the future. 50 Building upon these foundations, we sought to harness the benefits of MLC catalysts under electrochemical conditions, aiming to overcome the hurdles associated with alcohol oxidation in the presence of amines while mitigating the undesirable outcomes of alcohol overoxidation, undesired amine oxidation or competitive amine dehydrogenation.…”
Section: Resultsmentioning
confidence: 99%
“…In pursuit of a more sustainable future, a notable trend has emerged in the development of chemical transformations catalyzed by earth-abundant metals (EAMs). Distinguished from noble metals, EAMs offer the combined advantages of cost-effectiveness and low toxicity . A recent innovation was introduced to novel EAM complexes (e.g., Fe, Co, and Mn), wherein both the metal center and the coordinated ligand participated in the bond activation under relatively mild conditions and displayed exceptional activity and selectivity in organic reactions (Scheme a), ,, which was named metal–ligand cooperation (MLC). The MLC activation mode was only well-established in homogeneous catalysts, such as the M–L mode observed in the well-known Noyori catalysts and the (de)­aromatization mode represented by Milstein catalysts. However, these homogeneous catalysts bear inherent limitations, including air sensitivity, costly coordination ligands, and challenges in postreaction recyclability. , …”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33] In recent work, we showed that non-thermal, electrochemical pathways can be used to activate metal-ligand cooperative (MLC) [34][35][36] catalysts for endergonic dehydrogenation reactions at room temperature. 37,38 This prompted us to explore whether non-thermal MLC chemistry could also be leveraged for catalytic benzene carbonylation. Following a mechanistic approach, we seek to identify, understand and overcome bottlenecks in photochemical carbonylative C-H activation promoted by MLC systems, with the goal of providing novel alternatives for catalytic benzene carbonylation.…”
Section: Introductionmentioning
confidence: 99%